Comparison of K-ras mutations in lung, colorectal and gastric cancer - PENG, NANQIU (D.A. Spandidos, 2014)
K-ras is involved in the EGFR pathway that regulates cell survival, motility and proliferation, as well as angiogenesis and metastasis. It is also essential for carcinogenesis. The K-ras mutation status can be used to predict the therapeutic efficacy of targeted drugs such as cetuximab. The aim of this study was to compare K-ras mutation in different types of cancer. Nested and COLD-PCR were used to detect K-ras mutations. The Chi-squared test was used for statistical analysis. In this study, the total K-ras mutation frequency was found to be 9.09, 18.61 and 6.67% in lung, colorectal and gastric cancer, respectively. Similar K-ras mutation frequencies were detected among sample types and genders for lung and gastric cancer, with the exception of colorectal cancer. However, age had no impact on the K-ras mutation rates.